PERAN DINAS TENAGA KERJA KABUPATEN ASAHAN DALAM PENYELESAIAN PERSELISIHAN HAK PEKERJA/BURUH - Mangaraja Manurung (Magister Hukum Sekolah Pascasarjana Unida, 2022)
In the employment relationship there are workers/labor rights, commonly referred to as normative rights. Where it turns out that the practice is not fully implemented by the entrepreneur, many entrepreneurs actually carry out the normative rights of workers/laborers, which are still far below the applicable provisions, so that in the end it creates conflict. This research was carried out by looking at the truth in the field and by taking into account the provisions of the applicable norms which were then confirmed by the Asahan Regency employment agency. Disputes over the rights of workers/laborers that often occur are regarding the lack of wages which are carried out in conjunction with demands for payment of severance pay as a result of termination of employment. The settlement process still faces many obstacles.